ON SUBSPACE-DISK TRANSITIVITY OF BILATERAL WEIGHTED SHIFTS - Bamerni, Nareen; Kilicman, Adem (Malaysian Journal of Science, 2015)
In this paper, we give some properties of subspace-disk transitive operators and use them to characterize subspace-disk transitive bilateral weighted shifts in terms of their weight sequences. As a consequence, we show that a bilateral weighted shift is subspace-disk transitive if and only if it satisfies the subspace-diskcyclic criterion. Then, we give a much simpler condition for some other cases. Keywords: subspace-diskcyclic operators, subspace-disk transitive operators, weighted shifts